(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
It is proposed for consideration that madness is an escape. Based on the ideas of L. Binswanger’s existential analysis, psychopathology is seen as a specific way of life. The factors that induce and control ‘escape’ are analyzed. I consider the conditions of human life, which may cause a person ‘to escape into madness’ as a way out of intolerable circumstances.